Factors influencing working adults in Kuching City to purchase imitate product / Anirul Sufiszah Sulong - Sulong, Anirul Sufiszah (Faculty of Business and Management, 2018)
The growth of imitation business activities as well as the demand for the imitated product are keep arising. This research study aims to identify the factors influencing working adult in Kuching City to purchase imitated product. This study intends to examine the relationship of Price, Brand Name and social influence with purchase intention. Working adult between the age of 18 to more than 50 years old were selected randomly in Kuching City as respondents of analysis. 200 questionnaire were answered and valid for coding and analysis. Collected data were analyzed using SPSS version. The findings of this study show that all three elements have significant relationship with purchase intention. The results show that Price is the most critictical factor influencing working adult to purchase imitated product.